Financial analysis of pond area extension in Pacific white shrimp culture at Cantigi Indramayu - Iis Diatin; U. Kusumawardany (Jurnal Akuakultur Indonesia)
Pacific white shrimp is one of the primadona of fishery commodities. This shrimp is superior as it resists to diseases and also high productivity. Jati Hasil Diri (JHD) located in Cantigi Indramayu is one of the pacific white shrimp culture company. In order to develop the business, this company planned to extent their pond area from 26 to 42 Ha. This plan was therefore needed to be financially analyzed to confirm its feasibility. There were two different scenarios of area extension, first scenario was to extent pond area without any technical improvement, and the second scenario was to extent pond area with technical improvement. The result of the study shows that the pond area extension was feasible with NPV of Rp7.221.427.150,00  and  Rp29.867.006.067,00, the net B/C of  2,62 and 7,7  and  also the  IRR of 47,84%  and 146,55% for the first and second scenario, respectively. Sensitivity analysis indicated that the business is still feasible to be operated at a maximal of feed price the increase of 38,84% for the first scenario and 119,36% for the second scenario or if the shrimp price decrease with a maximum decrease of 18,81% and 41,12% at first and second scenario, respectively. The first business scenario is more sensitive as compare to the second scenario.